The historical responsibility of General Studies in a context of global collapse and civilizational crisis. - Paniagua Vega, Esteban (2024)
Introduction. In the introduction to the article we set out how the global collapse and the current civilizational crisis imply the need for a permanent reflection on the role of general studies and the impulse in the academic formation of a new humanism that criticizes and overcomes the ideological prejudices of liberal humanism. Objective. The general objective of the article is to provide a propaedeutic contribution to address the issue of the responsibility of general studies to continue promoting a new humanism. Discussion. The discussion starts from a critical description of the failure of liberal humanism or that analyticaland colonial interpretation of the history of European and American thought from which a hegemonic and western identity was sought to be defined during the second half of the 20th century. Conclusions. After making this critical exposition, some general and exploratory reflections on the importance of education and generalstudies in the process of forming critical thinking of people capable of authentically acing our own societies are presented as conclusions.